The influence of superheated injection on liquid and gaseous flow field of an experimental single-hole gasoline direct injection injector. (February 2021) - Bornschlegel, Sebastian; Conrad, Chris; Durst, Alexander; Welss, Richard; Wensing, Michael; Olbinado, Margie; Helfen, Lukas; Baumbach, Tilo
In modern gasoline direct injection engines, the fuel is (partially) superheated for a significant proportion of the time during operation. This means that the vapour pressure of the fuel, or at least of many of its components, is higher than the ambient pressure inside the engine during injection. If the excess fuel enthalpy cannot be removed by evaporation at the free surface of the spray, the liquid phase boiling creates new surfaces. This phenomenon is known as flash boiling. Flash-boiling atomization produces smaller droplets and can therefore be beneficial as an additional atomization mechanism. Furthermore, it can reduce the penetration depth of a spray, although it also decreases the stability of fuel sprays. This is manifested in undesired targeting changes, that is, spray contraction due to jet-to-jet interaction. In extreme cases, a complete spray collapse can occur, where a multi-hole or hollow-cone spray contracts towards the spray axis and forms a jet-like structure that increases penetration depth. To understand the relationship between flash-boiling atomization and targeting changes, flash boiling was investigated with a single-hole generic injector without jet-to-jet interaction. In addition to macroscopic spray parameters, this study also focused on the flow field of the spray itself measured using laser Doppler anemometry, as well as the spray-induced flow field of the surrounding gas phase measured using fluorescent particle image velocimetry. The results show a strong radial expansion of the jet directly after nozzle exit, caused by internal flash boiling. It is shown that this expansion is caused by a zone of expanding fuel vapour in the centre of the spray. As a result, the displacement of air after injector opening as well as at the front of the spray is significantly increased, causing a decrease in spray front velocity and penetration depth. The stationary air entrainment, however, is only moderately increased as is the total amount of captured air, since the fuel vapour displaces air in the spray.